Pravni terminološki slovar - Dugar, Gregor; Fajfar, Tanja; Humar, Marjeta; Žagar Karer, Mojca; Novak, Aleš; Tičar, Luka; Jemec Tomazin, Mateja (Slovarji;Fran;Terminologišče, 2018)
The Dictionary of Legal Terminology' shows the conceptual system of modern Slovenian law. In more than 10,000 dictionary entries, we present the terminology of contemporary Slovenian legal science, legal practice and legislation after 1991. The dictionary is primarily intended for legal experts, who practice various professions (including judges, lawyers, notaries, prosecutors as well as heads of HR and legal departments in companies). It is also intended for students of law and related sciences, in order to familiarize them with the conceptual system of Slovenian law in a professionally relevant manner. In order to use the dictionary efficiently at least a basic knowledge of law is required. This does not mean that journalists, translators, proof-readers and others who encounter legal terminology cannot use it. However, it should be borne in mind that definitions contained in a terminological dictionary are very concise and sufficiently informative only for an expert who is familiar with the conceptual system of a specific field of study, while other users are provided with a suitable starting point so they can find additional information if necessary.